Heat-conducting gel and preparation method thereof

By using a combination of graphene-coated diamond, vinyl silicone oil and ceramic fillers, the problem of insufficient thermal conductivity of existing thermal interface materials is solved, and efficient heat dissipation and electrical insulation are achieved, making it suitable for electronic equipment.

CN120818339APending Publication Date: 2025-10-21SHANGHAI ALLIED PLASTIC IND
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202510901297.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-07-01
Publication Date
2025-10-21

AI Technical Summary

Technical Problem

Existing thermal interface materials have insufficient thermal conductivity, high hardness, easy aging and powdering, and poor insulation. They cannot meet the needs of efficient heat dissipation and pose the risk of local overheating or short circuit.

Method used

Diamond with a graphene coverage rate of 60-85% is used as a thermal conductive filler, combined with vinyl silicone oil and ceramic fillers to form a high-efficiency thermal conductive network, improve thermal conductivity and electrical insulation, improve filler dispersion and wettability, reduce viscosity, and enhance extrusion and hardness.

Benefits of technology

Significantly improve the thermal conductivity, hardness and extrusion rate of thermal conductive gel, increase breakdown voltage, ensure electrical insulation, and meet the efficient heat dissipation needs of electronic equipment.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The invention relates to the technical field of heat-conducting materials, in particular to heat-conducting gel and a preparation method thereof. The heat-conducting ceramic composite material comprises the following components in parts by weight: 80-120 parts of a heat-conducting filler, 70-100 parts of a ceramic filler, 1-3 parts of vinyl silicone oil and 0.5-5 parts of an auxiliary agent, the auxiliary agent comprises a modifier; the heat-conducting filler comprises modified diamond, and the modified diamond comprises diamond with the graphene coating rate of 60-85%. The heat conductivity of the heat-conducting gel obtained through a specific formula and the preparation method can reach 20 W / mk or above, the extrusion rate can reach 30 g / min, the hardness after curing can reach shore0030-50, and the breakdown voltage can be larger than 6 kV / mm.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of thermal conductive materials, and in particular to a thermal conductive gel and a preparation method thereof. Background Art

[0002] As electronic devices become increasingly miniaturized and their internal components become more highly integrated, their performance and functionality continue to improve, leading to significantly increased heat generation. This makes efficient heat dissipation crucial for ensuring stable device operation. This is especially true as 5G technology upgrades drive thinner, lighter, and more powerful smartphones, and as the optical module industry introduces high-performance products like the 1.6T, the pursuit of lightweight and highly integrated designs has severely squeezed the heat dissipation space. Existing thermal interface materials, due to their insufficient thermal conductivity, are unable to meet this demand. Furthermore, existing high-thermal conductivity materials commonly suffer from defects such as high hardness, aging-induced powdering, and poor insulation. These issues not only fail to fundamentally address the problem but can also pose risks of localized overheating or short circuits.

[0003] Chinese invention patent application CN119799012A discloses a method for preparing a single-component curable thermally conductive gel with a high extrusion rate of 12W. A trimethoxy-terminated side vinyl silicone oil is subjected to a hydrosilylation reaction with a hydrogen-terminated silicone oil, and a thermally conductive filler is added to form a mixture. The mixture is then subjected to high-temperature treatment to hydrolyze the hydroxyl groups and trimethoxy groups on the surface of the powder to produce methanol, which evaporates at high temperatures. This allows the vinyl silicone oil to directly wrap around the surface of the thermally conductive powder, reducing the viscosity of the oil-powder mixture and thereby increasing the thermal conductivity. However, the thermal conductivity of the thermally conductive gel of this invention is only 10W / (m·K), which limits its application scenarios. Summary of the Invention

[0004] A first aspect of the present invention provides a thermally conductive gel, comprising, by weight, 80-120 parts of a thermally conductive filler, 70-100 parts of a ceramic filler, 1-3 parts of a vinyl silicone oil, and 0.5-5 parts of an auxiliary agent; the auxiliary agent includes a modifier; the thermally conductive filler includes modified diamond, and the modified diamond includes diamond with a graphene coverage rate of 60-85%.

[0005] This study found that thermally conductive fillers, including diamonds with a graphene coverage of 60-85%, can simultaneously improve the thermal conductivity, hardness, extrusion rate, and breakdown voltage of thermally conductive gels. First, diamonds themselves have extremely high intrinsic thermal conductivity. The combination of the two forms a highly efficient thermally conductive network. The graphene coating reduces phonon scattering and interfacial thermal resistance, significantly improving overall thermal conductivity. Furthermore, the optimized range of graphene coverage of 60-85% ensures uniform coverage of the diamond surface, avoiding both interface defects caused by insufficient coverage and conductive paths that may form due to excessive coverage, thereby maintaining high electrical insulation. The insulating properties of graphene form a barrier on the diamond surface, inhibiting the conduction path and increasing the breakdown voltage. Simultaneously, the rigid structure of the diamond and the reinforcing effect of the graphene coating improve the interfacial bonding between the filler and the vinyl silicone oil matrix, improving the filler's dispersibility and wettability, and reducing filler agglomeration. This enhances the gel's fluidity and reduces its viscosity during processing, making it easier to extrude and fill small gaps. In addition, the combination of ceramic filler and modified diamond synergistically forms a thermal conductive path, while the flexibility of the vinyl silicone oil matrix balances the overall hardness and avoids excessive embrittlement.

[0006] The thermally conductive filler further comprises at least one of spherical diamonds, shaped diamonds, and angular diamonds.

[0007] Optionally, the thermally conductive filler further includes at least two of spherical diamonds, shaped diamonds, and angular diamonds.

[0008] Optionally, the thermally conductive filler further includes spherical diamonds and shaped diamonds.

[0009] The modified diamond is added in an amount of 50-90 wt % in the thermal conductive filler.

[0010] Optionally, the modified diamond is added to the thermal conductive filler in an amount of 70-85 wt %.

[0011] The ceramic filler includes at least one of aluminum oxide, zinc oxide, and aluminum nitride.

[0012] The particle size of the thermal conductive filler is 20-150 μm.

[0013] Optionally, the particle size of the thermally conductive filler is 50-150 μm.

[0014] Optionally, the particle size of the thermally conductive filler is 50-120 μm.

[0015] Optionally, the spherical diamond is selected from one of the following particle sizes: 80 μm, 100 μm, and 120 μm.

[0016] Optionally, the shaped diamond is selected from one of the following particle sizes: 20 μm, 50 μm, 80 μm, 120 μm, and 150 μm.

[0017] Optionally, the angular diamond is selected from one of the following particle sizes: 80 μm, 120 μm, and 150 μm.

[0018] Optionally, the modified diamond has a particle size of 100-150 μm.

[0019] The particle size of the ceramic filler is 0.2-150 μm.

[0020] Optionally, the particle size of the ceramic filler is 0.2-20 μm.

[0021] Optionally, the aluminum oxide includes at least one of spherical aluminum oxide and single crystal aluminum oxide.

[0022] Optionally, the alumina includes spherical alumina and single crystal alumina, and the weight ratio of the single crystal alumina to the spherical alumina is (2-6):1.

[0023] Optionally, the weight ratio of the single crystal alumina to the spherical alumina is (2-4):1.

[0024] The aluminum nitride includes at least one of spherical aluminum nitride and single crystal aluminum nitride.

[0025] Optionally, the aluminum nitride includes spherical aluminum nitride.

[0026] Optionally, the spherical alumina can be selected from one of the following particle sizes: 0.5 μm, 1 μm, 2 μm, 5 μm, 10 μm, 20 μm, 40 μm, and 70 μm.

[0027] Optionally, the single crystal aluminum oxide may be selected from one of the following particle sizes: 0.3 μm, 1.5 μm, 5 μm, 10 μm, 40 μm, 70 μm, and 90 μm.

[0028] Optionally, the zinc oxide may have a particle size selected from one of the following: 0.2 μm, 0.5 μm, and 1.2 μm.

[0029] Optionally, the spherical aluminum nitride may be selected from one of the following particle sizes: 2 μm, 10 μm, 20 μm, 80 μm, 100 μm, 120 μm, and 150 μm.

[0030] Optionally, the single crystal aluminum nitride may have one of the following particle sizes: 0.3 μm, 1.5 μm, 5 μm, 10 μm, 15 μm, and 20 μm.

[0031] The vinyl content in the vinyl silicone oil is 0.08-10 wt %.

[0032] Optionally, the vinyl content in the vinyl silicone oil is 0.4-3 wt%.

[0033] Optionally, the vinyl content in the vinyl silicone oil is 1-3 wt%.

[0034] The modifier includes at least one of octyltrimethoxysilane, dodecyltrimethoxysilane, n-octyltriethoxysilane, vinyltrimethoxysilane, hexamethyldisilazane, single-end reactive polydimethylsiloxane, and double-end reactive polydimethylsiloxane.

[0035] Optionally, the modifier includes octyltrimethoxysilane and dual-end reactive polydimethylsiloxane, and the weight ratio of the octyltrimethoxysilane to the dual-end reactive polydimethylsiloxane is 0.75:(0.8-1.5).

[0036] The vinyl silicone oil includes at least one of double-ended vinyl silicone oil, single-ended vinyl silicone oil, and side-chain vinyl silicone oil.

[0037] Optionally, the viscosity of the vinyl silicone oil at 25° C. is 20-500 mPa·s.

[0038] The auxiliary agent further comprises at least one of a cross-linking agent, an inhibitor, and a catalyst.

[0039] Optionally, the auxiliary agent further includes a cross-linking agent, an inhibitor, and a catalyst.

[0040] Optionally, the cross-linking agent includes at least one of terminal hydrogen-containing silicone oil, side hydrogen-containing silicone oil or terminal-side hydrogen-containing silicone oil.

[0041] Optionally, the viscosity of the cross-linking agent at 25° C. is 10-800 mPa·s.

[0042] Optionally, the inhibitor includes at least one of acetylene cyclohexanol, 1,1,3-triphenyl-2-propyn-1-ol, and methylbutynol.

[0043] Optionally, the catalyst comprises a platinum catalyst.

[0044] A second aspect of the present invention provides a method for preparing a thermally conductive gel, comprising the following steps:

[0045] Step 1: uniformly mix the modifier, vinyl silicone oil, ceramic filler, and thermal conductive filler to obtain a pre-treated base material;

[0046] Step 2: Mix the remaining components with the pre-treated base to obtain a thermally conductive gel.

[0047] Optionally, the method for preparing the thermally conductive gel comprises the following steps:

[0048] Step 1: Evenly mix the thermal conductive filler, modifier, and vinyl silicone oil, and then evenly mix with the ceramic filler to obtain a pre-treated base material;

[0049] Step 2: Mix the pretreated base material with the cross-linking agent and the inhibitor, then add the catalyst and mix evenly to obtain a thermal conductive gel.

[0050] Optionally, the step 1 specifically includes: first placing the thermal conductive filler into the bottom of the kneader, then adding the modifier, and then adding vinyl silicone oil, first stirring at 5 to 50 rpm for 5 to 30 minutes, scraping the wall of the equipment stirring paddle after the operation is completed, and then stirring for a second time, stirring at 5 to 50 rpm for 5 to 30 minutes, and the above operation needs to be performed 3 to 5 times until the material in the stirring tank is uniform, and after the last operation is completed, adding ceramic filler in 1-3 times (stirring at 5 to 20 rpm for 5 to 10 minutes, scraping the wall of the equipment stirring paddle after the operation is completed, and stirring again) and stirring evenly can be heated, the heating temperature is 135°C, and the inside of the kneader is kept in a vacuum state during the heating period, the vacuum degree is -0.1 MPa, and the duration is 30 to 180 minutes. Stir at a speed of 5 to 100 rpm during the heating period, and wait for the pot to cool to room temperature after heating to obtain the pretreated base material.

[0051] Optionally, the step 2 specifically includes: first passing cooling water through the kneader, setting the cooling water temperature to 10-25°C, first adding the crosslinker and inhibitor into the stirring tank, then adding the pretreated base material, and finally adding the catalyst, stirring at 10-50 rpm for 5-30 minutes, during which the cooling water is always on and the vacuum is turned on, the vacuum degree is -0.1 MPa, and the wall is scraped after the stirring is completed. The above operation needs to be performed 1-3 times (completing the stirring-scraping process is one time), and then stirring at 5-20 rpm for 10-60 minutes, turning on the vacuum during stirring, and obtaining the thermal conductive gel after the stirring is completed.

[0052] Beneficial effects

[0053] 1. The thermal conductive filler includes diamond with a graphene coverage rate of 60-85%, which can simultaneously improve the thermal conductivity, hardness, extrusion rate and breakdown voltage of the thermal conductive gel.

[0054] 2. The addition of modified diamond in the thermal conductive filler is 50-90wt%, which can improve the thermal conductivity of the thermal conductive gel.

[0055] 20W / (m·K).

[0056] 3. The thermally conductive filler also includes spherical diamonds and shaped diamonds, which can further increase the extrusion rate to >30g / min and the breakdown voltage to >6kV / mm on the basis of excellent thermal conductivity.

[0057] 4. The particle size of the thermal conductive filler is 50-150 μm and the particle size of the ceramic filler is 0.2-20 μm, which can further improve the hardness (Shore00) of the thermal conductive gel after curing to 30-50 on the basis of excellent thermal conductivity.

[0058] 5. The preparation method of the thermal conductive gel of this application is simple and meets the large-scale application requirements of electronic devices. DETAILED DESCRIPTION

[0059] Examples 1-5, Comparative Examples 1-3

[0060] A thermally conductive gel, the components of which are shown in Table 1 in parts by weight, wherein the components whose manufacturer's model is not disclosed are not limited to the manufacturer's model:

[0061] Table 1

[0062]

[0063] Among them, Examples 1-5 are diamonds with a graphene coverage rate of 80%, Comparative Example 1 is a diamond with a graphene coverage rate of 50%, Comparative Example 2 is a diamond with a graphene coverage rate of 90%, and Comparative Example 3 is a diamond with a graphene coverage rate of 100%.

[0064] In Example 1, Examples 4-5, and Comparative Examples 1-3, the particle size of spherical diamond is 100 μm, the particle size of shaped diamond is 50 μm, the particle size of single-crystal aluminum nitride is 10 μm, the particle size of single-crystal alumina is 1.5 μm, and the particle size of spherical alumina is 0.5 μm.

[0065] In Example 2, the particle size of spherical diamond is 80 μm, the particle size of shaped diamond is 50 μm, the particle size of single-crystal aluminum nitride is 15 μm, the particle size of single-crystal aluminum oxide is 5 μm, and the particle size of spherical aluminum oxide is 0.5 μm.

[0066] In Example 3, the particle size of spherical diamond is 80 μm, the particle size of shaped diamond is 20 μm, the particle size of single-crystal aluminum nitride is 10 μm, the particle size of single-crystal aluminum oxide is 2 μm, and the particle size of spherical aluminum oxide is 0.3 μm.

[0067] The modifiers are octyltrimethoxysilane and double-ended reactive polydimethylsiloxane, and the weight ratio of the octyltrimethoxysilane to the double-ended reactive polydimethylsiloxane is 0.75:1.

[0068] The vinyl silicone oil is a single-ended vinyl silicone oil (Guangdong Chensi New Material Technology Co., Ltd., cx-352-40cst, vinyl content: 1.74 wt%).

[0069] The inhibitor is acetylene cyclohexanol, and the catalyst is a platinum catalyst.

[0070] The cross-linking agent is hydrogen-terminated silicone oil (Shanghai Jingri, DH007).

[0071] A method for preparing a thermally conductive gel comprises the following steps:

[0072] Put the modifier, vinyl silicone oil, ceramic filler and high thermal conductivity filler into the kneader, wherein the high thermal conductivity filler is first put into the bottom of the kneader, and then the modifier is added, and then the vinyl silicone oil is added. Stir at 50 rpm for 5 minutes. After the operation is completed, scrape the wall of the equipment stirring paddle and stir for a second time. Stir at 50 rpm for 5 minutes. The above operation needs to be performed 4 times until the material in the stirring tank is uniform. After the last operation is completed, add the ceramic filler and stir at 20 rpm for 5 minutes. After the operation is completed, scrape the wall of the equipment stirring paddle and stir again. The above operation needs to be performed 2 times. After stirring evenly, heating can be carried out. The heating temperature is 135°C, and the inside of the kneader is kept in a vacuum state during the heating period. The vacuum degree is -0.1 MPa and the duration is 100 minutes. Stir at a speed of 50 rpm during the heating period. After the heating is completed, wait for the pot to cool to room temperature to obtain the base material.

[0073] First, pass cooling water through the kneader, and set the cooling water temperature to 20°C. Add the crosslinker and inhibitor to the stirring tank, then add the base material, and finally add the catalyst. Stir at 50 rpm for 5 minutes. During stirring, the cooling water is always on and the vacuum is turned on. The vacuum degree is -0.1 MPa. After stirring is completed, scrape the wall. The above operation needs to be performed twice. Then stir at 20 rpm for 10 minutes. Turn on the vacuum during stirring. After stirring, a thermal conductive gel is obtained.

[0074] Performance testing methods

[0075] The thermally conductive gels prepared in the examples and comparative examples were subjected to the following performance tests, and the test data are listed in Table 2.

[0076] Thermal conductivity: measured according to ASTM D 5470-17 using a Ruiling LW-9389 interface material thermal resistance and thermal conductivity measuring device (at 25°C).

[0077] Hardness: measured using a shore 00 durometer (at 25°C) according to ASTM D2240.

[0078] Extrusion rate: measured according to ASTM D2452 using E3V-platform + X100 (30cc EFD hose, air pressure 90 psi, test time 60 s).

[0079] Breakdown voltage: measured according to ASTM D149 using a breakdown voltage tester (at 25° C.) with a voltage rise rate of 0.5 kV / min.

[0080] Performance test data

[0081] Table 2

[0082]

Claims

1. A thermally conductive gel, characterized in that: The components include, by weight, 80-120 parts of thermal conductive filler, 70-100 parts of ceramic filler, 1-3 parts of vinyl silicone oil and 0.5-5 parts of auxiliary agent; the auxiliary agent includes a modifier; the thermal conductive filler includes modified diamond, and the modified diamond includes diamond with a graphene coverage rate of 60-85%.

2. The thermally conductive gel according to claim 1, characterized in that The thermally conductive filler further comprises at least one of spherical diamonds, shaped diamonds, and angular diamonds.

3. The thermally conductive gel according to claim 1, characterized in that The thermally conductive filler also includes spherical diamonds and shaped diamonds.

4. The thermally conductive gel according to claim 1 or 3, characterized in that: The modified diamond is added in an amount of 50-90 wt % in the thermal conductive filler.

5. The thermally conductive gel according to claim 1, characterized in that The ceramic filler includes at least one of aluminum oxide, zinc oxide, and aluminum nitride.

6. The thermally conductive gel according to claim 1 or 5, characterized in that: The particle size of the thermal conductive filler is 50-150 μm.

7. The thermally conductive gel according to claim 6, characterized in that The particle size of the ceramic filler is 0.2-20 μm.

8. The thermally conductive gel according to claim 1, characterized in that The vinyl content in the vinyl silicone oil is 0.08-10 wt %.

9. The thermally conductive gel according to claim 1, characterized in that: The auxiliary agent further comprises at least one of a cross-linking agent, an inhibitor, and a catalyst.

10. A method for preparing the thermally conductive gel according to any one of claims 1 to 9, characterized in that: The following steps are involved: The modifier, vinyl silicone oil, ceramic filler and thermal conductive filler are uniformly mixed to obtain a pre-treated base material; and the remaining components are mixed with the pre-treated base material to obtain a thermal conductive gel.

Citation Information

Patent Citations

  • Preparation method of 12W single-component curable heat-conducting gel with high extrusion rate

    CN119799012A